Real Food, Real Facts: Processed Food and the Politics of Knowledge - Charlotte Biltekoff (University of California Press, 2024)
In recent decades, many members of the public have come to see processed food as a problem that needs to be solved by eating "real" food and reforming the food system. But for many food industry professionals, the problem is not processed food or the food system itself, but misperceptions and irrational fears caused by the public's lack of scientific understanding. In her highly original book, Charlotte Biltekoff explores the role that science and scientific authority play in food industry responses to consumer concerns about what we eat and how it is made. As Biltekoff documents, industry efforts to correct public misperceptions through science-based education have consistently misunderstood the public's concerns, which she argues are an expression of politics. This has entrenched "food scientism" in public discourse and seeded a form of antipolitics, with broad consequences. Real Food, Real Facts offers lessons that extend well beyond food choice and will appeal to readers interested in how everyday people come to accept or reject scientific authority in matters of personal health and well-being. "In this brilliant book, Charlotte Biltekoff deftly examines unexplored dimensions of the food wars and ultimately offers more nuanced thinking about science as the ultimate arbiter of fundamentally political decisions—a difficult but necessary challenge in a 'post-truth' world." — Julie Guthman, author of The Problem with Solutions "This is critical reading for scholars, consumers, and food industry professionals alike." — Anna Zeide, author of Canned "In lucid, accessible prose, Biltekoff employs the frames of Real Facts and Real Food to understand the twenty-first-century landscape of American food." — Amy Bentley, Professor of Food Studies, New York University
Keywords: 330; food; processed food; food industry